KESIAPSIAGAAN SUMBER DAYA MANUSIA PADA RUMAH SAKIT GIGI MULUT UNIVERSITAS SYIAH KUALA TERHADAP ANCAMAN BENCANA GEMPA BUMI - Muhammad Rais; Nazli Ismail; M. Dirhamsyah (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2017)
Hospital is one of the most important locations during a natural disaster happen. Natural disasters can be a serious situation for hospitals dealing with the number of casualties and therefore a specific hospital readiness is required. To know the preparedness of human resources in hospital against the threat of earthquake disaster, A research has been done at oral dental hospital of syiah kuala university. A total of 83 respondents were included in the questionnaires covering 69 clinical students, 8 faculty members, 3 medical officers and 3 medical personnel. Furthermore, in-depth interviews were conducted on five representatives from each of these sections for information and the results of the questionnaire given. The data completion instrument used is parameter questionnaire and index preparedness level that has been issued by LIPI-UNESCOISDR. The results show that human resource preparedness on the knowledge parameter is ready in the index of categories, while other parameters such as policy and strategy, emergency response plans, earthquake systems, and resource mobilization are on a category index not ready until almost ready. The results of interviews and observations also support the results of questionnaires that have been filled by the respondents. Thus, human resources preparedness at oral and dental hospital of syiah kuala university to the threat of earthquake disaster is in the index category less ready. This happens because the policies made to deal with the earthquake disaster are still minimal, the lack of sosialisation, training and the availability of special funding allocations to support the preparation of disaster emergency response. To improve human resource preparedness, it is necessary to evaluate thoroughly by forming a team and preparing disaster management procedures, and increasing socialization to all staff and clinic students.